2023
DOI: 10.3390/molecules28010396
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of a New FFAR1 Agonist—N-Alkylated Isobornylamine

Abstract: Free fatty acid receptor-1 (FFAR1) is one of the possible therapeutic targets in the search for new hepatoprotective drugs. FFAR1 agonists were found to have hypolipidemic, antifibrotic, anti-inflammatory, antiproliferative and antioxidant effects in addition to hypoglycemic action. In this work, we conducted a study of the hepatoprotective effect of the compound QS-528 (previously discovered as an agonist of FFAR1) at doses of 60, 90, 120 and 150 mg/kg on carbon tetrachloride (CCl4)-induced liver injury. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Like the compound SCO-267, QS-528 also resolved fatty liver dystrophy in mice in our experiment ( Figure 9 d) and reduced TG ( Figure 6 ) and ALT concentrations ( Figure 7 ). The observed hepatoprotective effect was also found earlier in a tetrachlomethane-induced model of liver injury [ 29 ]. It is worth noting that the compound SCO-267 was initially found to have hypoglycemic effects [ 30 ], followed by hepatoprotective effects [ 11 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Like the compound SCO-267, QS-528 also resolved fatty liver dystrophy in mice in our experiment ( Figure 9 d) and reduced TG ( Figure 6 ) and ALT concentrations ( Figure 7 ). The observed hepatoprotective effect was also found earlier in a tetrachlomethane-induced model of liver injury [ 29 ]. It is worth noting that the compound SCO-267 was initially found to have hypoglycemic effects [ 30 ], followed by hepatoprotective effects [ 11 ].…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, compound QS-619 is safe for long-term use, an extremely important characteristic of a potential drug [32]. The acute toxicity of compound QS-528 was studied previously at a dose of 1000 mg/kg and similar results were obtained [29].…”
Section: Discussionmentioning
confidence: 77%
“…Previously, we synthesized a (hydroxyphenyl)propanoic acid derivative QS-528 containing a terpene fragment, which was shown to have good affinity for the receptor discussed and also to induce a hypoglycemic effect in the oral glucose tolerance test (OGTT) with mice [24]. Further studies of this compound revealed other useful effects, as we propose, reduction of fatty degeneration of the liver and a hepatoprotective effect in mice [25,26]. Based on our results, we consider the structural analogs of QS-528 to be promising compounds for subsequent studies.…”
Section: Introductionmentioning
confidence: 93%
“…QS-528 has been shown to exhibit an affinity to FFAR1 during in vitro tests in the submicromolar concentration and also had a hypoglycemic effect in an oral glucose tolerance test (OGTT) on mice [9]. Further studies of this compound revealed other useful effects, such as reduction of fatty degeneration of the liver and a hepatoprotective effect in mice [10,11]. Based on our results, we consider the structural analogues of QS-528 to be promising compounds for the therapy of DM2.…”
Section: Introductionmentioning
confidence: 99%